IMPLEMENTATION OF NAÃVE BAYES CLASSIFICATION METHOD TO PREDICT GRADUATION TIME OF IBI DARMAJAYA SCHOLAR - Artaye, Ketut (Prosiding International conference on Information Technology and Business (ICITB), 2015)
Quality of a university can be seen in the average of howlong a collage student take to graduate, how long forgraduates to have a job also can be seen in study time inuniversity. Every university study time will variate withdifferent student in the university.Every major responsiblefor study development of scholars.They also have a task topredict study time length of every college student to decideand anticipate student who skip class that will cause a badresult in major performance.It is important to be done, especially in Informatics andBusiness Institute Darmajaya to maintain quality andperformance of each major. Because of that reason, writerdid research with title Implementation of NaÃ¯ve BayesClassification Method to Predict Graduation Time ofIBI Darmajaya Scholar to understand about averagestudy time of each college student.Key Words: NaÃ¯ve Bayes Classification, Predict, ScholarGraduation.